Ideological authenticity and the dynamics of suspicion - Eibach, Richard P.; Oakes, Harrison (Frontiers in Social Psychology, 2023)
Many episodes of political repression focus on policing ideological authenticity to distinguish true believers from mere pretenders. For insight into this phenomenon, we review a model wherein concerns about ideological inauthenticity and awareness of external incentives to feign ideological allegiances function to activate a suspicious mindset that leads perceivers to selectively attend to and police inauthenticity in their ideological comrades. We review dispositional and situational factors that amplify authenticity concerns as well as cues perceivers attend to when policing authenticity.